RISK IDENTIFICATION IN INCREASING THE ADDED VALUE OF KERUPUK AMPLANG AT KETAPANG DISTRICT - Putro, Haryo; Kurniati, Dewi; Oktoriana, Shenny (Fakultas Pertanian Universitas Tanjungpura, 2023)
The obstacles faced by IKM that want to add value to similar products are increasingly complex, especially the amplang IKMs in Ketapang Regency. In order to have good competitiveness with various problems, it is necessary to have an elaboration of value-added improvement activities. then survey activities were carried out to find 9 IKMs, then compiled a questionnaire by making closed questions to Amplang IKM owners by violating the restrictions during production activities. on production risks such as machine breakdown, work environment discomfort, work accidents and requests such as contracts not going according to plan, demand for amplang fluctuates, competitors for amplang products. Furthermore, researchers seek to formulate several methods from experts in mitigating risk, namely using FMEA calculations so that they can prioritize the highest risk, namely the demand for ampalng which fluctuates by 28.87 because the IKM predicts orders from big holidays, using the ordering method via Whatsapp media, when Currently, IKM is trying to use social media, but it is difficult to access because using Google Mail which seems complicated, so IKM continues to use Whatsapp media as well as promotional media.